ANALISIS PENGARUH KECEPATAN POTONG TERHADAP LAJU PENGERJAAN MATERIAL PADA PROSES PEMBUBUTAN BAJA AISI 1045 - Erick wiratama; Zaldy Kurniawan; Masdani Masdani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Metal working processes can be generally classified into 2, namely non-cutting (without cutting) and cutting (cutting). In the world of manufacturing industry, the success of a production process is greatly influenced by the production machines used. Lathes are machine tools used to cut rotating objects. The purpose of this study was to determine the effect of cutting speed, infeed speed, and cutting depth on the material processing rate using CNMG 120404-TF iscar brand lathe and using dromus as coolant. This study uses an experimental method, with variable settings in order to obtain a large material processing rate. The turning process uses a conventional MAWItech D.O.O.B 160 x1000 lathe, and the material used is AISI 1045, and the research data is analyzed using ANAVA in statistical software. The results showed that the effect of cutting speed on the mean material processing rate was -4.32% and the S / N ratio was -2.50%. The depth of cutting has the most significant effect on the rate of material processing.